Physico-chemical parameters and phytoplankton diversity of Netravathi - Gurupura Estuary, Mangalore, South west coast of India - Murugan S; Anandhi Usha D (International Journal of Life Sciences, 2017)
Water samples were collected from Netravathi estuary, Gurupura estuary and estuarine mouth with plankton collection net and different physico-chemical parameters were measured simultaneously to understand the Biophysicochemical conditions as they are important biological indicator of water quality. In the present study one-hundred and nineteen species in six divisions of phytoplankton were recorded. The maximum percentage of species were from division Bacillariophyta (77.31%), followed by Dinoflagellata (10.92%), Cyanobacteria (5.04%), Chlorophyta (4.20%), Ochrophyta (1.68%), Heterokontophyta (0.84%) respectively. The most diverse genus was Chaetoceros and Coscinodiscus (10 species each). The greatest number of phytoplankton diversity was found in Netravathi estuary (93) followed by estuarine mouth (77) and Gurupura estuary (61). Variations in physico-chemical parameters were observed at different study sites. The study infers that the phytoplankton diversity and distribution are subject to changes in physico-chemical conditions of the ecosystem. Therefore a frequent monitoring of these ecosystems with its physico-chemical conditions and biological diversity is crucial to know the health of such globally threatened ecosystem.